If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 13)(x + 2) = 0 Reorder the terms: (13 + x)(x + 2) = 0 Reorder the terms: (13 + x)(2 + x) = 0 Multiply (13 + x) * (2 + x) (13(2 + x) + x(2 + x)) = 0 ((2 * 13 + x * 13) + x(2 + x)) = 0 ((26 + 13x) + x(2 + x)) = 0 (26 + 13x + (2 * x + x * x)) = 0 (26 + 13x + (2x + x2)) = 0 Combine like terms: 13x + 2x = 15x (26 + 15x + x2) = 0 Solving 26 + 15x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (13 + x)(2 + x) = 0Subproblem 1
Set the factor '(13 + x)' equal to zero and attempt to solve: Simplifying 13 + x = 0 Solving 13 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + x = 0 + -13 x = 0 + -13 Combine like terms: 0 + -13 = -13 x = -13 Simplifying x = -13Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {-13, -2}
| -7y+3=25 | | X/2-4-12 | | -5/9=-7/3x | | k/6=12 | | 4tan(4x)=4 | | x-6x=46 | | -x^2+120-3276=0 | | 16-1/26(2x)=8-1/26(x) | | 4r-6=-12-2r | | 3(2x-5)=2(5+3x) | | x-y=200 | | 4(x+7)+3(3x-7)=72 | | (3x+4)(4x+1)-(2x+3)(x+3)=(5x+2)(2x+1) | | 14x-18=12-6x | | -4x-150=66-12x | | 0.19y+0.06(y+6000)=1860 | | 8x+16y=640 | | 3/4*b=8 | | 5s=4 | | -7y+3= | | 6x-y=-23 | | -2u=-2/9 | | -6(-3y+6)-4y=5(y-8)-2 | | 7-2b=2b+6 | | Y=17-4y-2 | | x/4=5/12-6-x/15 | | -3v+6v=-20-1 | | 1/4(20d-16)=5d-4 | | -9+11=6x-8x | | X=21/5/8 | | 1/3(6-3a)=6 | | (2/(16x^2-4))-(2/(8x^2-8x-6)) |